2020
DOI: 10.1016/j.amsu.2020.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Surgeons and social media: The use of twitter hashtags at the Academic Surgical Congress 2015–2019: A cross sectional study

Abstract: Background The use of Twitter hashtags at medical conferences has revolutionized the way healthcare professionals interact and advance their education. We aim to investigate the scope of the Academic Surgical Congress's online reach and engagement through the use of Twitter hashtags #ASC from 2015 to 2019, by analyzing the number of impressions and tweets and retweets. Methods A cross sectional study of Twitter data through Symplur with the following conference hashtags… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
(28 reference statements)
0
5
0
1
Order By: Relevance
“…According to data collected by Symplur and published in the article by Santarone et al 15 , between 2015 and 2017 the ACSCC saw a steady and significant increase in the number of tweets: from 12,800 in 2015 to 18,300 in 2016 and 24,700 in 2017. However, in 2018 and 2019, tweets dropped significantly to 19,700 and 19,300, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…According to data collected by Symplur and published in the article by Santarone et al 15 , between 2015 and 2017 the ACSCC saw a steady and significant increase in the number of tweets: from 12,800 in 2015 to 18,300 in 2016 and 24,700 in 2017. However, in 2018 and 2019, tweets dropped significantly to 19,700 and 19,300, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Según los datos recogidos por Symplur y publicados así mismo en el artículo de Santarone et al 15 , entre los años 2015 y 2017 el ACSCC tuvo un aumento constante y significativo de tuits: de 12.800 en 2015 a 18.300 en 2016 y a 24.700 en 2017. Sin embargo, en 2018 y 2019 los tuits se redujeron significativamente a 19.700 y 19.300, respectivamente.…”
Section: Resultsunclassified
“…It should be noted that the decline in Twitter engagement over recent years found by our study is not isolated to just the EAST conference. Multiple studies have shown similar drops in Twitter engagement at Academic Surgical Congress (ASC) annual meetings, 3 American Association for the Surgery of Trauma (AAST) meetings, 4 and the American College of Surgeons Clinical Congress (ACSCC). 5 Our study on the EAST conference, in addition to these other studies, highlighted social media fatigue as one potential explanation for the drop in Twitter engagement identified at each surgical conference.…”
mentioning
confidence: 96%
“…However, we described additional factors that may also play a role in the drop of active twitter engagement such as the use of alternative social media platforms, 1 changes in overall twitter usage, 3 and lack of quality content. 3 We also offer several recommendations for how to improve Twitter engagement with surgical conferences, such as the creation of an organizational Twitter account, 1 promotion via physician influencers, 1,4,5 advertisement of meetings and related hashtags, 1,3-5 inclusion of interactive elements into tweets, 3,4 assigning a designated social media and communications team to promote and monitor social media activity, 4,5 creation of social media stations to improve ease of access, 4 and inclusion of interactive Twitter sessions into presentations. 4 One crucially important factor that may significantly impact Twitter engagement and knowledge dissemination is the quality, accuracy, and reliability of the information that is being shared.…”
mentioning
confidence: 99%
See 1 more Smart Citation